Objective Tumor Response of Hepatocellular Carcinoma Obtained by Transarterial Radioembolization with Iodine-131-Lipiodol Versus Transarterial Chemoembolization for Patients with and without Portal Venous Thrombosis: A Controlled Interventional Trial - Oliveira Ribeiro, Michele Costa de; Moda, Kerolyn Adorne; Alvarez, Matheus; Koga, Katia Hiromoto; Moriguchi, Sônia Marta; Carvalho, Fábio Cardoso; Pinheiro, Rafael Soares Nunes; Qi, Xingshun; Romeiro, Fernando Gomes (Academic radiology, 2024)
Hepatocellular carcinoma (HCC) treatment often requires transarterial chemoembolization (TACE). However, TACE efficacy is controversial in the presence of portal vein thrombosis (PVT). Although transarterial radioembolization (TARE) benefit was previously documented in PVT, neither the objective tumor response (OTR) after TARE with Iodine-131-lipiodol ( I-lipiodol) nor the PVT effect on the results of locoregional therapies was accurately measured in prospective clinical trials. The aim of this study was to compare OTR and survival obtained by TARE with I-lipiodol versus TACE in patients with cirrhosis and HCC, as well as between those with and without PVT. 33 patients were included, from whom 38 tumors were assessed. OTR was quantified by a special algorithm to measure hypervascular HCC tissue. 19 tumors received each therapy. Nine subjects (27%) had PVT, most of them in the TARE group (p = 0.026). Mean OTR according to the tumor volumes was 24.2% ± 56% after TARE and 32.8% ± 48.9% after TACE, with no difference between the treatments (p = 0.616). Similar values were also observed between those with and without PVT (p = 0.704). Mean survival was 340 days and did not differ between the two treatments (p = 0.596), but was 194 days in PVT cases (p = 0.007). This is the first study in which OTR obtained by TARE with I-lipiodol is accurately measured. Additionally, PVT impact on survival after TARE and TACE was precisely documented. Although the TARE group had more PVT subjects (who had shorter survival), TARE and TACE achieved similar OTR and OS rates.